For k ∈ R − { − 1 } , n → ∞ lim j = 1 ∑ n ( n k + j ) ( n + 1 ) 1 − k j = 1 ∑ n j k = 6 0 1
Find k .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I think summation j^k = j^(k+1) / k+1 . Not j+1
Notice that n → ∞ lim j = 1 ∑ n ( n k + j ) ( n + 1 ) 1 − k j = 1 ∑ n j k
= n → ∞ lim n 2 [ j = 1 ∑ n 1 / n ( j / n ) ] + n 2 k n k + 1 / ( n + 1 ) k − 1 j = 1 ∑ n 1 / n ( j / n ) k
= ∫ 0 1 x d x + k ∫ 0 1 x k d x × lim n → ∞ ( n / ( n + 1 ) ) k + 1 = 1 / 6 0
Problem Loading...
Note Loading...
Set Loading...
Assuming k as a positive integer, one can write:
1 k + 1 = ( 0 + 1 ) k + 1 = C k + 1 0 ⋅ 0 k + 1 + C k + 1 1 ⋅ 0 k ⋅ 1 + C k + 1 2 ⋅ 0 k − 1 ⋅ 1 2 + . . . + C k + 1 k + 1 ⋅ 1 k + 1
2 k + 1 = ( 1 + 1 ) k + 1 = C k + 1 0 ⋅ 1 k + 1 + C k + 1 1 ⋅ 1 k ⋅ 1 + C k + 1 2 ⋅ 1 k − 1 ⋅ 1 2 + . . . + C k + 1 k + 1 ⋅ 1 k + 1
3 k + 1 = ( 2 + 1 ) k + 1 = C k + 1 0 ⋅ 0 k + 1 + C k + 1 1 ⋅ 2 k ⋅ 1 + C k + 1 2 ⋅ 2 k − 1 ⋅ 1 2 + . . . + C k + 1 k + 1 ⋅ 1 k + 1
⋮
( n + 1 ) k + 1 = C k + 1 0 ⋅ n k + 1 + C k + 1 1 ⋅ n k ⋅ 1 + C k + 1 2 ⋅ n k − 1 ⋅ 1 2 + . . . + C k + 1 k + 1 ⋅ 1 k + 1
Summing it all up, one ends up with:
( n + 1 ) k + 1 = ( k + 1 ) j = 1 ∑ n j k + O ( n k )
j = 1 ∑ n j k = k + 1 ( n + 1 ) k + 1 + O ( n k )
So:
n → ∞ lim ∑ j = 1 n ( n k + j ) ( n + 1 ) 1 − k ∑ j = 1 n j k
= n → ∞ lim n k ∑ j = 1 n 1 + ∑ j = 1 n j ( n + 1 ) 1 − k ⋅ [ k + 1 ( n + 1 ) k + 1 + O ( n k ) ]
Since n goes to ∞ :
= n → ∞ lim n 2 k + 2 n 2 + n ( n + 1 ) 1 − k ⋅ [ k + 1 ( n + 1 ) k + 1 ]
= n → ∞ lim ( 2 k 2 + 3 k + 1 ) n 2 + ( k + 1 ) n 2 n 2 + 4 n + 2
= 2 k 2 + 3 k + 1 2
Since it equals 6 0 1 :
2 k 2 + 3 k + 1 = 1 2 0
2 k 2 + 3 k − 1 1 9 = 0
k = 7 or k = − 8 . 5
Since we assumed k as a positive integer:
k = 7